2014
DOI: 10.1530/joe-14-0445
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon secretion after metabolic surgery in diabetic rodents

Abstract: Excessive or inadequate glucagon secretion promoting hepatic gluconeogenesis and glycogenolysis is believed to contribute to hyperglycemia in patients with type 2 diabetes. Currently, metabolic surgery is an accepted treatment for obese patients with type 2 diabetes and has been shown to improve glycemic control in Goto-Kakizaki (GK) rats, a lean animal model for type 2 diabetes. However, the effects of surgery on glucagon secretion are not yet well established. In this study, we randomly assigned forty 12-to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…5C), suggesting that gastric bypass surgery results in a significant increase of a-cells. Enhanced fasting glucagon levels and post-surgery glucagon secretion have been observed in animal and human studies (Jorgensen et al 2012, Eickhoff et al 2014. In the present study and others using the GK rat model (Saeidi et al 2013), fasting blood glucose level was not notably altered following RYGB, presumably because of the increase of a-cells and enhancement of fasting glucagon response.…”
Section: Discussionsupporting
confidence: 61%
“…5C), suggesting that gastric bypass surgery results in a significant increase of a-cells. Enhanced fasting glucagon levels and post-surgery glucagon secretion have been observed in animal and human studies (Jorgensen et al 2012, Eickhoff et al 2014. In the present study and others using the GK rat model (Saeidi et al 2013), fasting blood glucose level was not notably altered following RYGB, presumably because of the increase of a-cells and enhancement of fasting glucagon response.…”
Section: Discussionsupporting
confidence: 61%
“…This finding was unexpected, as both glucose 13 and GLP-1 14 inhibit glucagon release, and since the 30 min postprandial concentrations of glucose was increased after SG and the GLP-1 concentrations after 30 and 120 min were increased after SG and RYGB. Others have also found that postprandial glucagon secretion was not inhibited by meals or glucose after gastric bypass despite higher GLP-1 secretion in patients 1517 or in rats after gastric sleeve or gastric bypass surgeries 18 . This suggest that the SG patients may have an impaired inhibitory effect of glucose on glucagon secretion (alpha-cell resistance), which has been observed in an alpha-cell model of insulin resistence 13 .…”
Section: Discussionmentioning
confidence: 97%
“…Another study demonstrated an early attenuation of the glucagon response to a mixed meal early after both LSG and RYGB, but fasting glucagon levels were similar to preoperative values at 1 year after either operation type [13]. Rodent models of LSG also find reduced fasting glucagon, as well as an augmented response following meal stimulation and improved glucagon: insulin ratio that is superior to RYGB [37]. Considered together with our results, most data suggest that LSG provides early and ongoing significant improvement in glucagon levels in both overt clinical T2DM and subclinical insulin resistance in the obese.…”
Section: Discussionmentioning
confidence: 99%